2021
DOI: 10.1039/d0ra09004b
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion forces drive water oxidation in molecular ruthenium catalysts

Abstract: Rational design of artificial water-splitting catalysts is central for developing new sustainable energy technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…Although the present O 2 end -on configuration differs from the typical side -on coordination in Ni-O 2 complexes of other dioxygenases, the proposed O 2 – splitting process resembles a Criegee rearrangement in non-heme iron intradiol dioxygenases, as well as an alkylperoxo-intermediate observed in extradiol-ring cleaving dioxygenases . Moreover, similar peroxo-intermediates have been proposed for O–O bond splitting in oxidoreductases like cytochrome c oxidase or apocarotenoid oxygenase (see Figure S10 for comparison to AsqJ), as well as in enzymatic and molecular H 2 O-splitting catalysts, such as photosystem II , and Ru-catalysts, respectively.…”
Section: Discussionsupporting
confidence: 58%
“…Although the present O 2 end -on configuration differs from the typical side -on coordination in Ni-O 2 complexes of other dioxygenases, the proposed O 2 – splitting process resembles a Criegee rearrangement in non-heme iron intradiol dioxygenases, as well as an alkylperoxo-intermediate observed in extradiol-ring cleaving dioxygenases . Moreover, similar peroxo-intermediates have been proposed for O–O bond splitting in oxidoreductases like cytochrome c oxidase or apocarotenoid oxygenase (see Figure S10 for comparison to AsqJ), as well as in enzymatic and molecular H 2 O-splitting catalysts, such as photosystem II , and Ru-catalysts, respectively.…”
Section: Discussionsupporting
confidence: 58%
“…Proceeding by a I2M pathway, an electron-withdrawing group on 1 causes destabilization of the Ru V = O species, favoring the O-O bond formation. For catalysts following WNA pathway, Rodriguez et al (2021) reported that increasing electron-withdrawing ability can facilitate the nucleophilic attack at the Ir V intermediate (a rate-determining step), therefore enhance the catalytic activity of [Cp*Ir (Xpic)NO 3 ], as indicated by the correlations between σ and the measured TOF max . Yoshida et al (2010) and Abdel-Magied et al (2017) reported that for single-site Ru complex, a more electron-donating substituent affords a smaller oxidation potential of Ru center and enhances its catalytic activity.…”
Section: C6h4xmentioning
confidence: 99%
“…In addition to aforementioned intermolecular interactions, Timmer et al (2021) discovered that off-set interactions that introduced by de-symmetrization of the axial ligands in complex 16 and 17 (Figure 7A) can provide enough space for the O-O bond formation and reduce reaction barrier. DFT calculations suggested that reduced kinetic barrier of the second-order O-O bond formation ensures high catalytic performance especially at low catalyst concentrations.…”
Section: Off-set Interactionsmentioning
confidence: 99%
See 2 more Smart Citations